2021
DOI: 10.3390/en14020329
|View full text |Cite
|
Sign up to set email alerts
|

Energy Evaluation of a PV-Based Test Facility for Assessing Future Self-Sufficient Buildings

Abstract: In recent years, investigations on advanced technological solutions aiming to achieve high-energy performance in buildings have been carried out by research centers and universities, in accordance with the reduction in buildings’ energy consumption required by European Union. However, even if the research and design of new technological solutions makes it possible to achieve the regulatory objectives, a building’s performance during operation deviates from simulations. To deepen this topic, interesting studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A modular Lithium-ion BESS is implemented in the simulation environment by employing a Python class as defined in the literature (Amato et al 2021;Brandi et al 2022b) that simply emulates the BESS operation by estimating the SOC BESS since the BESS degradation is not considered. However, this approach is sufficiently accurate for conducting an initial assessment of the effects of BESS installation.…”
Section: Implementation Details On Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A modular Lithium-ion BESS is implemented in the simulation environment by employing a Python class as defined in the literature (Amato et al 2021;Brandi et al 2022b) that simply emulates the BESS operation by estimating the SOC BESS since the BESS degradation is not considered. However, this approach is sufficiently accurate for conducting an initial assessment of the effects of BESS installation.…”
Section: Implementation Details On Case Studymentioning
confidence: 99%
“…Moreover, to safeguard the health of the battery and optimise its performance, SOC levels are bounded by minimum and maximum values, as indicated by the manufacturer. For a Li-ion BESS technology, these values are set respectively at 10% and 90% of the total capacity, allowing for a total Depth of Charge (DoC)/Depth of Discharge (DoD) of 80% (Amato et al 2021).…”
Section: Implementation Details On Case Studymentioning
confidence: 99%
“…The result indicated that the proposed system provided indoor temperature on mild and severe winter season and free-floating mode achieved the best thermal comfort than other modes. Investigating the interactions effects between the building envelope and the HVAC systems is fundamental to maintain the NZEBs [183].…”
Section: Economic Considerations Of Bipvmentioning
confidence: 99%
“…the best thermal comfort than other modes. Investigating the interactions effects between the building envelope and the HVAC systems is fundamental to maintain the NZEBs [183]. The prerequisite information of technology, performance, and the parameters to operate and design the integrated HVAC and domestic hot water (DHW) production systems for buildings were presented by [184].…”
Section: Economic Considerations Of Bipvmentioning
confidence: 99%
“…Savolainen and Lahdelma [10] study optimized control by managing thermal storage and batteries on the basis on the coming 15 min power balance settlement. Amato et al [11] and Kotarela et al [12] demonstrate that the local use of photovoltaic energy can be enhanced thanks to batteries and local energy sharing, to obtain self-sufficient buildings, near to nZEB parameters. Similarly, in [13,14], the benefit of renewable energy communities in the self-consumption (SCF) of PV production emerges.…”
Section: Introductionmentioning
confidence: 99%